Jesus' death and heavenly offering in Hebrews - Jamieson, Bobby (Society for New Testament studies monograph series, 2019)
This book addresses two crucial, related questions in current research on the Epistle to the Hebrews: when and where did Jesus offer himself? And what role does Jesus' death play both in Hebrews' soteriology as a whole, and specifically in Jesus' high-priestly self-offering? The work argues that the cross is not when and where Jesus offers himself, but it is what he offers. After his resurrection, appointment to high priesthood, and ascent to heaven, Jesus offers himself to God in the inner sanctum of the heavenly tabernacle, and what he offers to God is the soteriological achievement enacted in his death. Hebrews figures blood, in both the Levitical cult and the Christ-event, as a medium of exchange, a life given for life owed. Represented as blood, Christ's death is both means of access and material offered: what he achieved in his death is what he offered to God in heaven